2019
DOI: 10.1002/gps.5057
|View full text |Cite
|
Sign up to set email alerts
|

Carer insights into self‐harm in the very old: A qualitative study

Abstract: Objective To examine the insights of carers to better understand self‐harm in their older relatives. Methods An in‐depth interview was conducted with the nominated relative/friend (carer) of a person over 80 who had self‐harmed within the last month. Carer interpretation and experience of the self‐harm and clinical care were explored qualitatively. Audio recordings were transcribed and the content thematically analyzed using N‐VIVO. Results Thirty‐two carers of 30 older people who self‐harmed were interviewed.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
43
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(46 citation statements)
references
References 25 publications
1
43
0
2
Order By: Relevance
“…This "what do you expect" societal attitude possibly fuels patient, carer, and GP nihilism and leads to a passive tolerance of suicide in older people. Regardless, the disconnect between patients, carers, GPs, and specialist mental health services was strongly evident and still manifested by frank "suicidal secrets" as we (Wand et al, 2019) and others (Draper et al, 2018) have identified previously, as well as avoidance, denial, and the difficulty asking for help. Such problems recognizing, communicating, or understanding emotions have been associated with both delay in seeking help for mental health problems (Epstein et al, 2010) and with suicide attempts in middle-aged populations (Levi et al, 2008).…”
Section: Discussionmentioning
confidence: 86%
See 4 more Smart Citations
“…This "what do you expect" societal attitude possibly fuels patient, carer, and GP nihilism and leads to a passive tolerance of suicide in older people. Regardless, the disconnect between patients, carers, GPs, and specialist mental health services was strongly evident and still manifested by frank "suicidal secrets" as we (Wand et al, 2019) and others (Draper et al, 2018) have identified previously, as well as avoidance, denial, and the difficulty asking for help. Such problems recognizing, communicating, or understanding emotions have been associated with both delay in seeking help for mental health problems (Epstein et al, 2010) and with suicide attempts in middle-aged populations (Levi et al, 2008).…”
Section: Discussionmentioning
confidence: 86%
“…Qualitative approaches that seek the perspective of the older person in understanding the meaning and intent of their self-harm may be especially informative (Van Orden, 2018). In our baseline qualitative studies, 30 people aged 80 + who had self-harmed, their carers, and general practitioners (GPs) were interviewed within a month following self-harm (Wand et al, 2018a;Wand et al, 2018b;Wand et al, 2019). Reasons for self-harm included communicating unmet and unarticulated needs, loneliness, disintegration of self, being a burden, helplessness with rejection, hopelessness, and endless suffering (Wand et al, 2018b).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations